Zakat Management from a Good Governance Perspective in Siak Regency (Study at the Zakat Collection Unit in Tualang District) - Yasmine, Fayza; As’ari, Hasim (CV. Rayyan Dwi Bharata, 2024)
To assist the government in closing the socio-economic gap in society, Muslims' zakat must be managed professionally as a source of income. society, Muslim zakat must be managed professionally as a potential resource. potential resources. To help manage zakat in the region, BAZNAS Siak Regency has built fourteen Zakat Utilization Units (UPZ). One of the UPZ with a low level of zakat collection is UPZ Tualang sub-district. The amount of zakat distributed and the number of Muslim population are not comparable, as well as the level of zakat collection. population is not comparable, so is the collection rate. If supported by good governance framework, optimal zakat management can be achieved. The purpose of this research is to provide an overview of Zakat Management in Siak Regency based on Good Governance. Management in Siak Regency based on Good Governance, especially in UPZ Tualang District. Tualang. The examination technique used is subjective exploration with a contextual investigation approach using contextual investigation approach by using the hypothesis of Great Administration hypothesis according to the Unified Country Improvement Program (UNDP) in Khairudin, Soewito, and Aminah (2021) which has 9 factors, namely Guidelines Cooperation, Order, Straightforwardness, Responsiveness, Located Agreement, Fair, Convincing and Effective, Responsibility, and Primary Vision. The results of the study concluded that the management of zakat, especially in the Zakat Collection Unit (UPZ) of Tualang District, was not optimal because of the nine principles of good governance, namely the principles of participation, responsiveness and accountability, which found three obstacles, namely low public knowledge about zakat, ineffective socialization, and amil was not focused on managing zakat. Based on the results of this research, it is hoped that the community can more involved in the management of zakat in UPZ Tualang Regency, and the UPZ administrators are expected to be more effective in managing zakat. UPZ administrators are expected to be more effective in carrying out their duties in managing zakat and educating the public about zakat. managing zakat and educating the public about zakat.